Spray printing of organic semiconducting single crystals - Grigorios-Panagiotis Rigas (Nature Portfolio, 2016)
The development of organic electronics calls for low-cost printing techniques that can prepare high quality, large-area organic single crystals. Here, Rigaset al. achieve this goal by combining spray printing and antisolvent crystallization and test the method on various materials and substrates.